Pengaruh Mengasuh dan Mengasihi Dari Rumah Pada Ibu-ibu Muda Terhadap Kemampuan Kognitif Anak Usia 5-6 Tahun - Maghfiroh, Shofia; Suryana, Dadan (Perkumpulan Pengelola Jurnal PAUD Indonesia, 2022)
Parenting and loving children by communicating between mothers and children will have an impact on the potential and abilities of children. Cognitive abilities can train children including problem solving skills, abstract thinking and learning from an experience. The purpose of this research is to describe how the influence of nurturing and loving from home on young mothers on children's cognitive abilities. The method used is a qualitative research with descriptive analysis and a sample of 20 young mothers of children in class B1. Data collection techniques in the form of instruments, observations, and interviews. While the data analysis with data reduction stages, data models, and drawing conclusions. The results of the study obtained that young mothers already have the ability but have not been implemented optimally. How to care for and love children from home will have an impact on the cognitive abilities of the next child. With the conclusion that the activities of Parenting and Caring From Home for Young Mothers on Children's Cognitive Ability in Al-Hidayah Kindergarten, Pekanbaru, Regency can have a significant effect.